Decidual natural killer cell receptor expression is altered in pregnancies with impaired vascular remodeling and a higher risk of pre-eclampsia. Issue 1 (7th November 2014) - Wallace, Alison E; Whitley, Guy S; Thilaganathan, Baskaran; Cartwright, Judith E
Abstract : HLA-interacting cell surface receptors are altered on decidual natural killer cells in pregnancy, potentially altering interactions with fetal cells via chemokine expression. Abstract: During pregnancy, a specialized type of NK cell accumulates in the lining of the uterus (decidua) and interacts with semiallogeneic fetal trophoblast cells. dNK cells are functionally and phenotypically distinct from PB NK and are implicated in regulation of trophoblast transformation of the uterine spiral arteries, which if inadequately performed, can result in pregnancy disorders. Here, we have used uterine artery Doppler RI in the first trimester of pregnancy as a proxy measure of the extent of transformation of the spiral arteries to identify pregnancies with a high RI, indicative of impaired spiral artery remodeling. We have used flow cytometry to examine dNK cells isolated from these pregnancies compared with those from pregnancies with a normal RI. We report a reduction in the proportion of dNK cells from high RI pregnancies expressing KIR2DL/S1, 3, 5 and LILRB1, receptors for HLA-C and HLA-G on trophoblast. Decreased LILRB1 expression in the decidua was examined by receptor blocking in trophoblast coculture and altered dNK expression of the cytokines CXCL10 and TNF- α, which regulate trophoblast behavior. These results indicate that dNK cells from high RI pregnancies may display altered interactions with trophoblast via decreased expression of HLA-binding cell-surface receptors, impacting on successful transformation of the uterus for pregnancy.